The family treasury of Jewish holidays - Drucker, Malka; Patz, Nancy (Boston : Little, Brown, 1994)
Recounts the history and rituals of ten Jewish holidays, including appropriate games, recipes, and songs.
Includes bibliographical references (p. 177) and index.
Elem. School Library Collection.
Publisher's Weekly.
Booklist.
6.5
5-8
Keywords: Fasts and feasts -- Judaism -- Juvenile literature; Judaism -- Customs and practices -- Juvenile literature; Fasts and feasts -- Judaism; Judaism -- Customs and practices; Judaism -- Customs and practices; Religious holidays; Fasts and feasts -- Judaism; Judaism -- Customs and practices